IMPACT OF BRISK WALKING AND PRANAYAMA ON SYSTOLIC BLOOD PRESSURE OF MIDDLE AGED TAMILNADU POLICE OFFICERS - Dr. D. Kalidoss; Duggirala Subhashini; Mr. M.Karthik Prakash; Mr. Gulsan Kumar Behera; Ms. Harsha Sharma (The Bioscan, 2024)
The purpose of this study was to determine the effects of brisk walking and pranayama training on the systolic blood pressure (SBP) of Tamil Nadu police officers aged 40-50 years. A total of forty-five police officers from Villupuram district participated in the study. The participants were divided into three groups: a control group and two experimental groups. Group I (N=15) received brisk walking training, Group II (N=15) underwent pranayama training, and Group III (N=15) served as the control group without any specific intervention. The training program lasted for twelve weeks, during which the systolic blood pressure of all participants was measured both before and after the intervention. Data were statistically analyzed using covariance analysis to determine the significance of the interventions. The results indicated that both brisk walking and pranayama training had a significant positive effect on the systolic blood pressure of the police officers, with participants in the experimental groups showing considerable improvement compared to the control group. The findings suggest that incorporating physical activities like brisk walking and pranayama into the daily routine of police officers could be an effective strategy for managing and reducing systolic blood pressure, thereby enhancing cardiovascular health.